THU0297 A novel ultrasound scoring system for giant cell arteritis. (15th June 2017) - Monti, S; Ponte, C; Carrara, G; Rumi, F; Hutchings, A; Dasgupta, B; Luqmani, R
Abstract : Background: Colour duplex sonography (CDS) can be used for giant cell arteritis (GCA) to detect inflammatory oedema of the vascular wall, known as "halo". A standardized, quantitative score to grade the severity and extension of vascular involvement detected by CDS has not yet been developed. Objectives: To develop and test different scoring models of CDS findings in patients with new onset GCA, and to correlate the models with final diagnosis, histologic findings, and outcome. Methods: We selected patients with a positive CDS and a confirmed diagnosis of GCA from the Temporal Artery Biopsy vs Ultrasound in Diagnosis of GCA (TABUL) study (1). We designed CDS models combining different ultrasonographic information based on available evidence, or hypothesized clinical relevance of size, anatomical distribution, and extent of halos, summing up to a final numeric score. Results: We included 135 GCA patients (male/female: 43/92), age 73.3±8. Fourty four patients (24%) had a positive CDS, but not a final diagnosis of GCA. We designed 8 different CDS models (Figure 1 ). Models 1, 4, 6, and 7 were significantly associated with a confirmed diagnosis of GCA (Table 2). Model 7 better discriminated patients with GCA from non-GCA: area under the curve (AUC): 0.844 (0.766–0.923). All, except models 5 and 8, correlated with a temporal artery biopsy (TAB) result diagnostic for GCA. Most models correlated with histologic findings involving the media or transmural infiltrate, but not with small vessel or adventitial involvement. None of the models correlated with permanent ischaemic sequelae, however, the low number of events might have affected the results. Conclusions: The CDS findings that better correlate with a diagnosis of GCA, and TAB findings are: the number of positive sites, the size of the halo (maximum, rather than average thickness), and the presence of bilateral halos, variably combined into a unique score. We plan to test these models in a new cohort of patients with suspected GCA, to determine their validity. References: Luqmani R, Lee E, Singh S, et al. The Role of Ultrasound Compared to Biopsy of Temporal Arteries in the Diagnosis and Treatment of Giant Cell Arteritis (TABUL): a diagnostic accuracy and cost-effectiveness study.Health Technol Assess 2016;20:1–238. Disclosure of Interest: None declared